2017
DOI: 10.1063/1.4977006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced infrared-to-visible up-conversion emission and temperature sensitivity in (Er3+,Yb3+, and W6+) tri-doped Bi4Ti3O12 ferroelectric oxide

Abstract: Strong up conversion (UC) luminescence at 527, 550, and 662 nm is compared under an excitation of 980 nm in single doped (Er3+), co-doped (Er3+/Yb3+), and (Er3+/Yb3+/W6+) tri-doped bismuth titanate (Bi4Ti3O12). For the co-doped system, the frequency (UC) emission intensity due to Er3+ ions is enhanced significantly in the green bands due to the efficient energy transfer from Yb3+ to Er3+ ions. Further increase in the emission intensity is seen with non-luminescent W6+ ions in the tri-doped system due to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Adding the higher working voltage for the current injection, the PE of the MOSLED with 10 Yb cladding cycles is relatively lower. These efficiencies are superior to that from Si‐based EL devices in literature . As revealed in previous reports, by using a thicker luminescent layer, the EL instensity and efficiency might be further increased, further optimization addressing the current injection issue would promote the potential application of these Al 2 O 3 :Yb,Er MOSLEDs in Si‐based optoelectronics.…”
mentioning
confidence: 85%
“…Adding the higher working voltage for the current injection, the PE of the MOSLED with 10 Yb cladding cycles is relatively lower. These efficiencies are superior to that from Si‐based EL devices in literature . As revealed in previous reports, by using a thicker luminescent layer, the EL instensity and efficiency might be further increased, further optimization addressing the current injection issue would promote the potential application of these Al 2 O 3 :Yb,Er MOSLEDs in Si‐based optoelectronics.…”
mentioning
confidence: 85%
“…In addition, it had been revealed that the emission intensity of RE ions-doped uorides and oxides can be modied with the addition of transition metals such as molybdenum (Mo) and tungsten (W). 10,11 Bokolia et al 12 pointed out that the UC emission intensity of Bi 4 Ti 3 O 12 : Er/Yb/W single crystal was signicantly enhanced with W doping by a distortion in the crystallographic symmetry. However, few reports on the effects of transition metals on the luminescence properties of RE ions -doped ferroelectric ceramics are found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, the emission intensity of Yb 3+ and Er 3+ co‐doped UC materials is affected by many factors, such as rare earth ion doping concentration, 24 shape and size of particles, 5 local crystal field around rare earth ions, 1 and so on. Tailoring the local crystal field around rare earth ions by ion doping or substituting the original composition of host with different ions is an effective method to improve the UC luminescence efficiency 25‐27 . Furthermore, some extra doping ion, such as Fe 3+ , will boost the UC luminescent properties and thermometric properties simultaneously 17,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Tailoring the local crystal field around rare earth ions by ion doping or substituting the original composition of host with different ions is an effective method to improve the UC luminescence efficiency. [25][26][27] Furthermore, some extra doping ion, such as Fe 3+ , will boost the UC luminescent properties and thermometric properties simultaneously. 17,28 Cubic pyrochlore Y 2 Ti 2 O 7 with low phonon energy (<712 cm −1 ) and stable physical and chemical properties is verified to be a good candidate host for efficient UC emission.…”
mentioning
confidence: 99%